Common core literacy for math, science, and technical subjects strategies to deepen content knowledge (grades 6-12) - McKnight, Katherine Siewert (Jossey-Bass teacher, 2015)
"According to the Common Core State Standards, which have been adopted by 46 states, students must develop literacy skills not just in English/Language Arts but across all content areas. This means that educators must teach literacy--reading, writing, speaking, listening, and language--in subjects like Math, Science, Social Studies, and Technology/Computer Science. This book help teachers understand what literacy looks like in math, science, and technology classrooms and shows them how to develop these literacy skills in their students. Author Katie McKnight is a popular education consultant who trains teachers nationwide on Common Core literacy. Features include: Alignment of activities to the Common Core State Standards in Interdisciplinary Literacy Difficulty Dial: A quick reference to determine the complexity of each activity Tips for Classroom Implementation: An overview of each literacy activity and how the tool supports the development of literacy skills and builds content knowledge Student Samples: Useful references for teachers across subjects and grade levels"--Provided by publisher.